A field guide to the Jewish people : who they are, where they come from, what to feed them, what they have against foreskins, how come they carry each other around on chairs, why they fled Egypt by running straight to a large body of water, and much more. Maybe too much more - Barry, Dave; Mansbach, Adam, 1976-; Zweibel, Alan (Flatiron Books, 2019)
Why do random Jewish holidays keep springing up unexpectedly? Why are yarmulkes round? Who was the first Jewish comedian? What's "Christian humor" and have you ever even heard of that phrase? Who is "the Golem" and whom do you want it to beat up? These baffling questions and many more are answered by comedy legends Dave Barry, Adam Mansbach, and Alan Zweibel, two-thirds of whom are Jewish. In A Field Guide to the Jewish People the authors dissect every holiday, rite of passage, and tradition, unravel a long and complicated history, and tackle the tough questions that have plagued Jews and non-Jews alike for centuries. Combining the sweetness of an apricot rugelach with the wisdom of a matzoh ball, this is the last book on Judaism that you will ever need. So gather up your chosen ones, open a bottle of Manischewitz, and get ready to laugh as you finally begin to understand the inner-workings of Judaism.